Breast Cancer Awareness, Screening Practices, and Perceived Barriers Among Female Undergraduate Students: An Institution‐Based Cross‐Sectional Study - Md. Mayin Uddin Hasan; Mohammad Injamul Hoq; Rijuana Ireen Tanju; Md. Jakaria; Mohammed Abu Sayeed (Cancer Reports)
ABSTRACT Background Breast cancer is a significant worldwide public health issue that poses a substantial threat to the lives of countless people around the world. Increasing awareness and implementing screening for breast cancer are two of the crucial strategies for decreasing the burden of disease. The study assessed awareness, practice, and perceived barriers to breast cancer screening among university students. Method An institution‐based cross‐sectional study was conducted from June 2023 to December 2023 at the International Islamic University Chittagong (IIUC), Bangladesh, where 387 students were randomly selected for this study. Result Among 387 participants, the majority (25.06%) were from the faculty of business administration, whereas 23.51% were from the faculty of science and engineering. Most (80.41%) of respondents had sufficient awareness of breast cancer and its screening. While they were aware of breast cancer screening, majority (67.7%) did not practice it. Students of law faculty were about three times [AOR: 0.31 (95% CI: 0.118–0.828)] and students of business administration faculty were about five times [AOR: 0.21 (95% CI: 0.087–0.532)] less likely to be aware of breast cancer and Breast Self Examination (BSE) than faculty of science and engineering. Also, living in dormitory students were more than two times [AOR: 0.42 (95% CI: 0.189–0.940)] less likely to be aware of breast cancer and screening of breast than those living with family. The majority (52.2% to 79.33%) of the students did not correctly identify different warning signs of breast cancer. Perceptions of having “no signs & symptoms,” not having “sufficient organization working on screening,” and “lack of awareness program” were found to be leading barriers to breast screening among students. Conclusion Though better awareness about breast cancer and its screening was found among the students, low practices were observed in screening. Students of the science and engineering faculty demonstrated a sufficient level of breast cancer awareness than students from other faculties, and students with good screening practice habits of breast cancer were sufficiently aware of breast cancer than poorly practicing students. Still, warning signs of breast cancer are unfamiliar to female students among university students. Frequent awareness campaigns are essential to train the students at regular intervals.